1996
DOI: 10.1007/bf00139764
|View full text |Cite
|
Sign up to set email alerts
|

Organic soil amendments in relation to nematode management with particular reference to India

Abstract: The addition of organic materials to soil has been used in managing plant-parasitic nematodes and has resulted in increased crop yield. Research on the utilization of waste materials such as oilseed cakes, chitin, compost, livestock and poultry manures, and cellulosic wastes appears promising for reducing populations of plant-parasitic nematodes. Nitrogen based amendments, plant phenolics, nematotoxic chemicals, development of predators and parasites of nematodes and microorganism stimulation have been conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…2). These results are consistent with many studies that have shown that organic amendments increase soil fertility such as SOM, TN, nitrate-N, AP and AK content (Akhtar and Mahmood 1996;Cai and Qin 2006;Chan et al 2007;Long et al 2015;Mohammadi Torkashvand et al 2015;Guo et al 2016;Seleiman and Kheir 2018; Wrobel-Tobiszewska et al 2018). As Table 1 shows, the nutrient level of the three organic materials were in the order of biochar > coconut husk > bagasse.…”
Section: Soil Fertility and Organic Materials Returnsupporting
confidence: 90%
See 1 more Smart Citation
“…2). These results are consistent with many studies that have shown that organic amendments increase soil fertility such as SOM, TN, nitrate-N, AP and AK content (Akhtar and Mahmood 1996;Cai and Qin 2006;Chan et al 2007;Long et al 2015;Mohammadi Torkashvand et al 2015;Guo et al 2016;Seleiman and Kheir 2018; Wrobel-Tobiszewska et al 2018). As Table 1 shows, the nutrient level of the three organic materials were in the order of biochar > coconut husk > bagasse.…”
Section: Soil Fertility and Organic Materials Returnsupporting
confidence: 90%
“…Organic amendments change the trophic structure, bulk density and pH of soil (Akhtar and Mahmood 1996). Soil bulk density tends to decrease probably because of the presence of nondecomposed organic materials in the soil (Jones et al 2011;Mohammadi Torkashvand et al 2015), while variation in pH depends on the type and amount of the amendment (Montemurro et al 2007;Dharmakeerthi et al 2012;Luo et al 2014).…”
Section: Soil Bulk and Ph Influenced By Organic Amendmentsmentioning
confidence: 99%
“…On the other hand, soil amended with oil-cakes of neem and other plant products have been successfully used for the control of plantparasitic nematodes [92,[97][98][99][100][101][102][103]. Whilst, fewer juveniles penetrated the roots of plants raised in neem cake amended soil compared to untreated plants [104].…”
Section: The Activity Of Azadirachtin On Plant Parasitic Nematodesmentioning
confidence: 99%
“…However, the most researches were focused on the root-knot nematodes, Meloidogyne spp. (Muller and Gooch, 1982;Alam, 1990;Akhtar and Mahmood, 1996;Nahar et al, 1996;Akhtar and Malik, 2000;Kheir, et al, 2000;Sundararaju et al, 2003;Verma, andKhan, 2004;Abdul Latif, et al, 2006;Wani, 2006;Ahmad, et al, 2007;Ibrahim, et al, 2007;Radwan, et al, 2007;Rather, et al, 2008;Ibrahim and Traboulsi, 2009;Kagai, 2009;Hussain, et al, 2011;Moosavi, 2012;Parihar et al, 2012;Ishaku and Ahaji, 2013;Ojo and Umar, 2013;Youssef andLashein, 2013 andSaeed andShawkat, 2014).…”
Section: Introductionmentioning
confidence: 99%